A review of model on malware detection and protection for the distributed control systems (Industrial control systems) in oil & gas sectors. (19th May 2019) - Yask,; Kumar, B. Suresh
Abstract: This paper reviews the state of the art of field Malware Detection and Protection for the Distributed Control Systems particularly in Oil & Gas Sectors with a focus on industrial control system applications. This paper is reviewing the existing Malware Detection and Protection for the Distributed Control Systems on the basis of malware detection. Control systems are system of electronic components that control the physical operations of machines – basically encompassing all digital systems that interact with the physical world. There are various types of control systems which are classified according to the use and application - Process Control Systems (PCS), Cyber Physical Systems (with actuators and sensors), Supervisory Control and Data Acquisition (SCADA) systems, Distributed Control Systems (DCS) etc. The malware detected in whole industrial area operating through integrated network is quite hard to recognize. The functional barrier at each step of process need to inform malware detection through the protection process.